(untitled) (Journal of Science Foundation, 2013)
The paper provides an overview of Bangladesh populations displaced by river erosion. The study describes the physical environmental conditions of the study area with a special attention to natural disasters of the region. It focuses the socio-demographic profile of the victims of the study area. Caused riverbank erosion a considerable proportion of the victims are compelled to leave the original homestead plot and take shelter by the road side embankment, neighbors land and relative land. The health condition of the victims is very low. Since the natural environmental situations, the economic crisis and poverty have been found to be related to natural disaster like riverbank erosion, so in this decade of environment the policy makers and researcher at the national level need to be aware of the magnitude of the environmental conditions of the riverbank erosion victims. In fact that, caused riverbank erosion every year unemployment, landless and poverty are increasing which is responsible to country wide unstable condition. DOI: http://dx.doi.org/10.3329/jsf.v8i1-2.14627 J. Sci. Foundation, 8(1&2): 55-65, June-December 2010